2016
DOI: 10.1016/j.bpj.2016.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sphingomyelin Clusters by Raman Spectroscopy

Abstract: Sphingomyelin (SM) is a major sphingolipid in mammalian cells that forms specific lipid domains in combination with cholesterol (Chol). Using molecular-dynamics simulation and density functional theory calculation, we identified a characteristic Raman band of SM at ∼1643 cm(-1) as amide I of the SM cluster. Experimental results indicate that this band is sensitive to the hydration of SM and the presence of Chol. We showed that this amide I Raman band can be utilized to examine the membrane distribution of SM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…By analogy with PE, the small headgroup size of CPE has been proposed to play a critical role to facilitate the strong CPE-CPE interaction 16 . This is in line with our recent report of stronger amide bond interaction between CPE molecules compared to SM molecules 17 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…By analogy with PE, the small headgroup size of CPE has been proposed to play a critical role to facilitate the strong CPE-CPE interaction 16 . This is in line with our recent report of stronger amide bond interaction between CPE molecules compared to SM molecules 17 .…”
Section: Discussionsupporting
confidence: 94%
“…In mammalian cells, sphingolipids such as SM, are thought to form specific “lipid raft” complexes with cholesterol (Chol) 1315 . In contrast to SM, CPE does not form complexes with Chol 16,17 , possibly due to the less favorable CPE-Chol interaction compared to SM-Chol. This difference has been attributed to the smaller size of the CPE headgroup and its reduced efficiency to shield the sterol molecule from unfavorable water interaction 8,18 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…3C), which is mainly composed of the CQO stretching modes of the amides, is sensitive to hydration and hydrogen bonding. 31 The formation of hydrogen bonds is connected with a red shift (towards smaller wavenumbers). It was observed that with increasing temperature the peak maximum slightly shifts to higher wavenumbers and the shoulder at 1650 cm À1 slightly decreases in intensity, which is a hint of weakening the hydrogen bond network (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They speculated that GNP-DPPE is entrapped in the subdomains, hampering its normal diffusion in the ordered domain. Moreover, fluorescent lifetime measurements 18 and Raman spectroscopy 19 revealed that SMs forms small aggregations in SM/dioleoylphosphatidylcholine (DOPC) binary bilayers, while fluorescent microscopy identified the macroscopic ordered/disordered phase separation in these mixtures 5 . These facts indicate that aggregations of SMs exist in macroscopic ordered domains 18 .…”
Section: Introductionmentioning
confidence: 99%